Analyzing the reduction quality of the distal radioulnar joint after closed K-wire transfixation in a cadaver model: is supination or neutral position superior? - Barbari, Jan el; Kohlhas, Laura; Franke, Jochen; Grützner, Paul Alfred; Schnetzke, Marc; Swartman, Benedict (Archives of orthopaedic and trauma surgery, 2024)
Distal radioulnar joint (DRUJ) instabilities are challenging and their optimal treatment is controversial. In special cases or when reconstruction of the stabilizing triangular fibrocartilage complex (TFCC) fails, K-wire transfixation can be performed. However, no consensus has been reached regarding the rotational position of the forearm in which this should be done. Therefore, it was investigated whether anatomical reduction would best be achieved by transfixation in neutral position or supination of the forearm.
Gesehen am 12.06.2024